PRODUÇÃO, CARACTERIZAÇÃO DE UMA NANOEMULSÃO CONTENDO SINVASTATINA E SUA AVALIAÇÃO NA EXCITOTOXICIDADE GLUTAMATÉRGICA - Moreira, Michele Pereira (2017)
Simvastatin is used to treat hypercholesterolemia acting by inhibition of 3-hydroxy-methylglutaryl-coenzyme A (HMG-CoA) reductase responsible for cholesterol synthesis. Studies carried out in humans, in animal models and in vitro observed neural damage reduction and increased glutamate uptake after simvastatin treatment. Glutamate is the major excitatory neurotransmitter in the central nervous system with crucial role in several physiological mechanisms, but at high levels it leads to cell death and participate to neurodegenerative diseases. Despite of pharmaceutical characteristics of simvastatin, as lipophilic drug that can cross cell membranes it has low bioavailability and non-specific biodistribution, simvastatin reach nervous system at low rates, limiting the pleiotropic effects described. Nanoemulsions may enhance solubility and increase biodistribution of lipophilic drugs, thus this technology can improve simvastatin performance in the neurodegenerative diseases treatment. The aim of study is producing simvastatin-loaded nanoemulsion, evaluate its physicochemical characteristics besides biological safety, and effect against glutamatergic toxicity. Blank nanoemulsion (without drug; BNE) and 1 mg/mL simvastatin nanoemulsion (SNE) were produced by spontaneous emulsification. Physicochemical characterization and stability were determined at three different temperatures (± 4 oC, ± 23 oC or ± 40 oC) for 15 days. Toxicity of formulations at 0.1 μg/mL; 1 μg/mL e 10 μg/mL was evaluated in Vero cell linage cultures and hippocampal slices from rat. Effect of formulations against glutamatergic excitotoxicity (10 mM glutamate) was evaluated at hippocampal slices from rat. All procedures with animals were previously approved by local Ethical Committee (CEUA no 05/2016). Formulation showed macroscopically homogeneous aspect and white color with Tyndall effect. Particle size was approximately 204 nm (BNE) and 139 (SNE). Zeta potential was -3 mV and -5 mV, for BNE and SNE respectively. Both of them appeared polydispersity index lower than 0.3, pH ± 6.5. Drug content was ± 1.01 mg/mL with encapsulation efficiency ± 98%. Formulations did not show any physicochemical alterations following 15 days at ± 23 oC or ± 40 oC, but simvastatin content was reduced. However, nanoemulsions exposed to ± 4 oC had constant drug content with increased particle size and polydispersity index. For all formulations, Zeta potential and pH were constant during 15 days. Cytotoxicity was no detected for all nanoemulsions. When hippocampal slices were incubated with glutamate with free simvastatin or SNE, 42% of cells were died, without effect of simvastatin. At the present work, nanoemulsions were produced efficiently, without cytotoxicity at parameters assayed. Additional studies should be performed to improve nanoemulsions stability. Simvastatin-loaded nanoemulsion or free did not show effect against glutamatergic damage evaluate in hippocampal slices from rat.